Pengaruh Leverage Terhadap Pertumbuhan Laba pada Perusahaan Manufaktur Sektor industri Dasar Kimia yang Terdaftar di Bursa Efek Indonesia Periode 2018-2022 - Melda A. Kasira; Srie Isnawaty Pakaya; Mohamad Agus Salim Monoarfa (Economic Reviews Journal, 2024)
This research aimed to determine the influence of Debt To Equity Ratio and Debt To Asset Ratio on Profit Growth in the Basic Industry and Chemical Sectors Listed on the Indonesian Stock Exchange in 2018-2022. The research samples were selected through purposive sampling, where 41 companies met the requirements as samples. The analytical test tool used to test this research was multiple linear regression. The data analysis applied the SPSS 27 application. The research findings indicated that the Debt To Equity Ratio (DER) influenced profit growth negatively, and Debt To Asset Ratio (DAR) influenced profit growth positively. In the meantime, simultaneously, the Debt To Equity Ratio (DER) and Debt To Asset Ratio (DAR) influenced profit growth.